Beyond patient contact: combined short- and long read sequencing reveals continuous occurrence of genomically related carbapenemase-producing Enterobacterales and plasmid mobility in a hospital, Germany, 2018 to 2021 - Claudia Stein (Eurosurveillance)
BACKGROUND Carbapenemase-producing Enterobacterales (CPE) frequently cause nosocomial outbreaks. To investigate these, tracing focused on patients with related CPE strains and spatiotemporal contact (e.g. contact with each other in a room or on a ward during overlapping periods) has limitations. Moreover, as widely available molecular typing methods cannot detect plasmid-related transmissions, carbapenemase gene transfer across enteric bacteria through plasmids in hospitals remains poorly understood. AIM Because whole-genome sequencing (WGS), particularly long-read sequencing, can offer insights into bacterial relationships both at core-genome and plasmid levels, we tested its utility, using VIM-CPE as example, to investigate plasmid and CPE spread in a hospital beyond outbreaks. METHODS We included inpatient episodes from 2018 to 2021 involving blaVIM-bearing CPE isolates. Short- and long-read WGS data were combined with patient movement information to identify genomically related hospital-acquired VIM-CPE and putative transmission routes. RESULTS Among 43 included inpatient episodes, 27 isolates were hospital-acquired, with 23 genomically related based on core-genome or plasmid analyses. For 14 of these 23 isolates, patient movement data supported suspected transmission events. Plasmid and core-genome level analyses revealed that most transmission events did not temporally concur, occurring over up to 33 months. Thus, conventional infection tracing methods focusing on concurrent spatiotemporal contact missed a substantial proportion of transmission events. CONCLUSION With our findings, we advocate for broader epidemiological investigations of temporal connections if genomic data suggest relatedness. We emphasise considering plasmid transfer alongside analyses of core-genome relatedness of bacteria beyond patient contact events to study CPE and resistance spread, and guide infection control strategies.